2009
DOI: 10.1007/978-3-642-04468-7_3
|View full text |Cite
|
Sign up to set email alerts
|

Why Are People’s Decisions Sometimes Worse with Computer Support?

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Abstract. In many applications of computerised decision support, a recognised source of undesired outcomes is operators' apparent over-reliance on automation. For instance, an operator may fail to react to a potentially dangerous situation because a computer fails to generate an alarm. However, the very use of terms like "over-reliance" betrays possible misunderstandings of these phenomena … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Because the data were sparse (26) the distributions of model deviances are not Chisquared and the standard analysis of deviance is not applicable. Therefore, we applied the le Cessie-van Houwelingen global test (27) to the null hypothesis of no difference between the observed responses and those estimated by the regression models [1] and [2]. For all sub-populations of cancers from rows and columns of Table 1, the le Cessie-van Houwelingen global test did not reject the null hypothesis for either of these two regression models, corroborating the validity of estimates obtained by these analyses.…”
Section: "Impact" Of Cad: Logistic Regression Estimatesmentioning
confidence: 61%
“…Because the data were sparse (26) the distributions of model deviances are not Chisquared and the standard analysis of deviance is not applicable. Therefore, we applied the le Cessie-van Houwelingen global test (27) to the null hypothesis of no difference between the observed responses and those estimated by the regression models [1] and [2]. For all sub-populations of cancers from rows and columns of Table 1, the le Cessie-van Houwelingen global test did not reject the null hypothesis for either of these two regression models, corroborating the validity of estimates obtained by these analyses.…”
Section: "Impact" Of Cad: Logistic Regression Estimatesmentioning
confidence: 61%
“…Thus, users may believe a system to be more reliable than it actually is and misuse it by agreeing with incorrect suggestions, a behavior known as over-reliance [3]. Previous studies have shown that over-reliance is widespread in CDSS use [2,4,14,25,26] and that it can be more pronounced in users with low confidence in their abilities or judgment [18]. This is a major concern when targeting a CDSS at clinicians who do not have specialized knowledge.…”
Section: A System Reliability and Usementioning
confidence: 96%
“…[17]. However, there is still a lack of knowledge about the impact of explanations on building trust and countering overreliance, as some research suggests that explanations lead to more correct decisions [9] whilst others suggest they can also lead to worse decision-making by the clinician [4].…”
Section: Introductionmentioning
confidence: 99%
“…177 This, coupled with our natural tendency toward automation bias, leads to the user's overconfidence and overreliance in the manufacturer's ability (or willingness) to ensure the security or reliability of their technologies. 178 Reasonably full disclosure on the part of the manufacturer, whether through regulatory, legislative, or private means, is a key factor in reducing these information gaps.…”
Section: Understand and Address The Technology Information Gapmentioning
confidence: 99%